[quotation] On the digital future - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
On the digital future: 'Our new telecentre will help our people because they lack information about producer prices and people will get information on agriculture, education, the nutrition of children and so on we also expect the centre to...